30-Day and 1-Year Mortality after Transcatheter Aortic Valve Replacement: The Impact of Balloon Aortic Valvuloplasty as a Bridging Therapy in a Portuguese Tertiary Center - Francisco B. Albuquerque; Bárbara L. Teixeira; André Grazina; Rúben Ramos; António Fiarresga; Alexandra Castelo; Tiago Mendonça; Inês Rodrigues; Duarte Cacela; Rui Ferreira (Journal of Interventional Cardiology)
Introduction. Since the advent and development of transcatheter aortic valve replacement (TAVR) in the contemporary era, balloon aortic valvuloplasty (BAV) has seen renewed interest. We aimed to compare 30-day and 1-year all-cause mortality between patients submitted to BAV as a bridging therapy before definite TAVR and patients submitted directly to TAVR. Methods. This was an observational, retrospective study of patients who underwent TAVR between 2009 and 2022 in a tertiary center. Patients with severe aortic stenosis (SAS) who underwent TAVR without prior BAV (woBAV group) and patients who were performed TAVR with prior BAV (wBAV group) as a bridging therapy were included. Primary endpoint was all-cause mortality at 30 days and 1 year after TAVR between wBAV and woBAV groups. Results. 800 patients were included, of which 767 were in woBAV group and 33 were in wBAV group. 30-day all-cause mortality rate was 21% in wBAV group compared to 4.4% in woBAV (unadjusted hazard ratio [HR], 5.19; 95% confidence interval [CI], 2.3–11.7, p < 0.001). At 1-year, all-cause mortality rate was 27% in wBAV group compared to 12% in woBAV group (unadjusted HR, 2.55; 95% CI, 1.28–5.10, p = 0.007). After covariate adjustments, mortality remained significantly higher in wBAV group. Conclusion. This study provides valuable insights into the outcomes of patients undergoing TAVR with prior BAV as bridging therapy, as these patients had higher mortality at 30 days and 1 year compared to patients direct to TAVR.